2020
DOI: 10.1038/s41467-020-19860-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid de novo evolution of lysis genes in single-stranded RNA phages

Abstract: Leviviruses are bacteriophages with small single-stranded RNA genomes consisting of 3-4 genes, one of which (sgl) encodes a protein that induces the host to undergo autolysis and liberate progeny virions. Recent meta-transcriptomic studies have uncovered thousands of leviviral genomes, but most of these lack an annotated sgl, mainly due to the small size, lack of sequence similarity, and embedded nature of these genes. Here, we identify sgl genes in 244 leviviral genomes and functionally characterize them in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…One such mechanism is de novo evolution, the birth of new genes from previously non-genic or intronic regions, which is now a widely acknowledged source of protein-coding and RNA genes [3][4][5]. Although de novo origination was once considered an unlikely event, catalogs of de novo genes have now been published for an expansive range of species [6][7][8][9][10][11][12][13]. Multiple models explain how protein-coding de novo genes may acquire both an open reading frame (ORF) and regulatory sequences permitting transcription [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One such mechanism is de novo evolution, the birth of new genes from previously non-genic or intronic regions, which is now a widely acknowledged source of protein-coding and RNA genes [3][4][5]. Although de novo origination was once considered an unlikely event, catalogs of de novo genes have now been published for an expansive range of species [6][7][8][9][10][11][12][13]. Multiple models explain how protein-coding de novo genes may acquire both an open reading frame (ORF) and regulatory sequences permitting transcription [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A 2 is highly asymmetric in shape and spans 110 Å in length while bound to the phage genome. The A 2 takes the position of a Cp-dimer and disrupts the perfect icosahedral symmetric shape of the capsid with the triangulation number of T = 3 [71][72][73]. The structural organization of the A 2 has two distinct regions, namely an α-helical part (with four-helix core) and a β stranded part (with seven-stranded sheet).…”
Section: Structure and Domainmentioning
confidence: 99%
“…Early studies on model ssDNA and ssRNA phages showed that native sgl genes are hard to identify through genomic approaches 12,15 . Sgls are typically small, embedded within other coding regions, and bear little sequence similarity to each other 3,[16][17][18] . Linking a gene to its mechanism of action has most often been accomplished using classical genetic selections 7,9 .…”
Section: Introductionmentioning
confidence: 99%